L-Arginine Improves Cognitive Impairment in Hypertensive Frail Older Adults - Mone, Pasquale; Pansini, Antonella; Jankauskas, Stanislovas S.; Varzideh, Fahimeh; Kansakar, Urna; Lombardi, Angela; Trimarco, Valentina; Frullone, Salvatore; Santulli, Gaetano (Frontiers in Cardiovascular Medicine, 2022)
Cognitive impairment is a very common event in hypertensive patients and in frail older adults. Endothelial dysfunction has been shown to underlie both hypertension and cognitive dysfunction. Our hypothesis is that L-Arginine, which is known to ameliorate endothelial dysfunction, could counteract cognitive impairment in a high-risk population of hypertensive frail older adults. We designed a single-blind, placebo-controlled, parallel-group, randomized trial to test the effects of 4-weeks oral supplementation of L-Arginine on global cognitive function of hypertensive frail older patients. The study was successfully completed by 35 frail hypertensive elderly patients assigned to L-Arginine and 37 assigned to placebo. At follow-up, we found a significant difference in the Montreal Cognitive Assessment (MoCA) test score between the L-Arginine treated group and placebo (p: 0.0178). We then demonstrated that L-Arginine significantly attenuated Angiotensin II-induced oxidative stress in endothelial cells. In conclusion, to the best of our knowledge, our study is the first to assess the MoCA score. Taken together, our findings indicate for the first time that oral L-Arginine supplementation improves cognitive impairment in frail hypertensive older adults.